Improved team cohesion and experience following geographical cohorting of clinician teams - Michael Scott; Christine Soong; Rebecca Ramsden; Luke Devine; Kate Van Den Broek; Alyssa Louis; Carolyn Farquharson; Katherine McQuaid-Bascon; Lisa Wayment (BMJ Open Quality)
Background Hospitalists frequently provide care to inpatients situated across numerous medical units, resulting in inefficiency, poor clinician experience and disjointed teamwork. We implemented geographical cohorting of clinician teams to improve team cohesion, efficiency and interprofessional team experience.Methods We conducted an interrupted time series study of medical inpatients at a single academic medical centre. Preintervention: July 2018–April 2019, intervention development: April 2019–May 2019 and the postintervention: June 2019–June 2020. The intervention included geographical cohorting of clinician teams onto dedicated inpatient medical wards, standardisation of unit-based interprofessional rounds and end-of-day unit-based huddles. The primary outcome was surveys of team experience and the secondary outcome was the number of pages to physicians (efficiency measure).Results A total of 6043 patients were included in the study: 2668 preintervention, 386 intervention development and 2989 postintervention. 3240 (53.6%) were female and two (<1.0%) were transgender. Postintervention versus preintervention team experience improved in: awareness of healthcare workers (HCWs) method to contact physicians (56.1% vs 19.0%, p<0.001), ease of contact of physician (82.5% vs 59.5%, p=0.001), timeliness of physician response (78.9% vs 61.9%, p=0.020), agreement of team on care plan (80.7% vs 73.8%, p=0.018) and care plan is communicated efficiently (71.9% postintervention vs 45.2% preintervention, p=0.005) and timely (68.4% postintervention vs 45.2% preintervention, p=0.003). Mean physician pages reduced by a postintervention estimate (factor) of −5.80 (95% CI: −6.30 to –5.29, p<0.001). Linear mixed-effects models of clinical patient outcomes demonstrated no significant changes.Conclusions Geographical cohorting of inpatient teams was associated with improved efficiency and team experience outcomes.